Evaluation of Financial Distress Prediction in the Telecommunications Industry Using the Ohlson and Taffler Model - Septiani, Novia Dwi; Iskandar, Rusdiah; Dewi, Catur Kumala (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
The company's large debt caused the company's operating income at PT Bakrie Telecom Tbk in 2020 - 2022 to decline because the company was unable to pay off its obligations and always had a negative net profit over several years, so the company had the potential to experience financial distress. The aim of this research is to determine and analyze the potential for financial distress at the company PT Bakrie Telecom Tbk using the Ohlson and Taffler model. This research uses quantitative methods with library research techniques, namely collecting data related to the problem to be researched to obtain secondary data. The analysis tool uses the Ohlson and Taffler model. The research results show that the Ohlson model predicts that PT Bakrie Telecom Tbk will experience bankruptcy with an O-Score value > 0.38 for the period 2020 to 2022. The Taffler model predicts PT Bakrie Telecom Tbk will be unhealthy with a T-Score value < 0.2 for the period 2020 to 2022 Based on the research results, it can be concluded that the Ohlson and Taffler model predicts that the company PT Bakrie Telecom will experience financial distress for the period 2020 - 2022.